1. Раскройте скобки:
а) 3(2а + в - 8с)
б) - 4 (-х +3у - 4 т)
2.У выражение:
а) 2(8,5 - х) - (7,8 - 5х)
б) 3(2х + 5) +2(3 – х) - 4
в) 7а – 4(2а – 3в) + (6в + а)(-3)
3. Найдите значение выражения -3(2а-3в) + 6(а – 2в) – 3а при а = -1, в = 5.
4. Вынесите общий множитель за скобки:
а) 8а - 8в;
б) 12ху + 18ах.
Пошаговое объяснение:1. Раскройте скобки:
а) 3(2а + в - 8с)
б) - 4 (-х +3у - 4 т)
2.У выражение:
а) 2(8,5 - х) - (7,8 - 5х)
б) 3(2х + 5) +2(3 – х) - 4
в) 7а – 4(2а – 3в) + (6в + а)(-3)
3. Найдите значение выражения -3(2а-3в) + 6(а – 2в) – 3а при а = -1, в = 5.
4. Вынесите общий множитель за скобки:
а) 8а - 8в;
б) 12ху + 18ах.
1. Раскройте скобки:
а) 3(2а + в - 8с)
б) - 4 (-х +3у - 4 т)
2.У выражение:
а) 2(8,5 - х) - (7,8 - 5х)
б) 3(2х + 5) +2(3 – х) - 4
в) 7а – 4(2а – 3в) + (6в + а)(-3)
3. Найдите значение выражения -3(2а-3в) + 6(а – 2в) – 3а при а = -1, в = 5.
4. Вынесите общий множитель за скобки:
а) 8а - 8в;
б) 12ху + 18ах.
Пошаговое объяснение:1. Раскройте скобки:
а) 3(2а + в - 8с)
б) - 4 (-х +3у - 4 т)
2.У выражение:
а) 2(8,5 - х) - (7,8 - 5х)
б) 3(2х + 5) +2(3 – х) - 4
в) 7а – 4(2а – 3в) + (6в + а)(-3)
3. Найдите значение выражения -3(2а-3в) + 6(а – 2в) – 3а при а = -1, в = 5.
4. Вынесите общий множитель за скобки:
а) 8а - 8в;
б) 12ху + 18ах.
3 - x = 1
- x = - 2
x = 2
ответ: x = 2.
2. lg(3x² + 12x + 19) - lg(3x + 4) = lg10
3x² + 12x + 19 = 10(3x + 4)
ОДЗ: 3x - 4 ≠ 0 | x ≠ 4/3
3x² + 12x + 19 = 30x + 40
3x² - 18x - 21 = 0 | /3
x² - 6x - 7 = 0
D = 36 - 4*1*(-7) = 36 + 28 = 64 = 8²
x₁ = (6 + 8)/2 = 7 x₂ = (6 - 8)/2 = - 1
ОДЗ: 3x + 4 > 0
x > - 4/3
x∈(-4/3; + бесконечность)
ответ: x = - 1; 7.
3. log₁₁((x + 4)*(x - 7)) = log₁₁(7 - x)
(x + 4)(x - 7) = 7 - x
x² - 7x + 4x - 28 = 7 - x
x² - 3x + x - 28 - 7 = 0
x² - 2x - 35 = 0
D = 4 - 4*1*(-35) = 4 + 140 = 144 = 12²
x₁ = (2 + 12)/2 = 7 x₂ = (2 - 12)/2 = - 5
ОДЗ: x + 4 > 0
x - 7 > 0
7 - x > 0
x∈(7; +бесконечность)
ответ: x∈∅
4. log₂x = t
t² - 4t + 3 = 0
D = 16 - 4*1*3 = 16 - 12 = 4 = 2²
x₁ = (4 + 2)/2 = 3 x₂ = (4 - 2)/2 = 1
ОДЗ: x > 0
ответ: x = 2; 8.